X-Ray Powder Diffraction Data for Tetragonal Zirconia Solid Solutions in System ZrO2-YTaO4 - Kim, D.-J. (1992)
Tetragonal zirconia (t-ZrCO2) can be stabilized with 15 to 22 mol% YTaO4. X-ray powder diffraction data for the end members of the solid solution series Zr0.76Y0.12Ta0.12O2 and Zr0.66Y0.17Ta0.17O2 are reported along with lattice parameters across the single phase region. These tetragonal zirconias are characterized by large tetragonalities (c/2a > 1.0203) and nontransformability to the monoclinic structure. ？ 1992, Cambridge University Press. All rights reserved.